PENGEMBANGAN MATERI CHARACTER BUILDING SISWA SMA/SEDERAJAT - Shidratul Attika; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Young generation have to know and understand their own characters. However, in fact, many of them have not known what kind of characters that they have. Characters must be built to be a human that has characteristics. Hence, the material services need to be develop to be a material for students’ character building that expected to be used by guidance and counseling teachers to be taught to the students. This study aims at (1) to arrange the material for students’ character building based on the clarity, the systematic, the supporting pictures, the instruments, the novelty of material, and the supporting of game and video, (2) to know the result of the students’ character building quality. The material is arranged by using research and development method, then it is experimented to the students with the time allocated is 4 lesson hours (4x40’). This material is validated by first and second guidance lectures, guidance and counseling teacher, 38 students of SMK Muhammadiyah 2, Pekanbaru. The material consists of the definition and the method of character building. The result of the material development shows that the quality of the material is in the “Very Good” category with the score 4,26 for the whole aspects of assessment.Keywords: Guidance and Counseling, Character Building, Senior High School